Effect of Endosulfan on Protein Content of Freshwater Bivalve Corbicula Striatella - Sunita Jadhav (International Journal of Research in Informative Science Application & Techniques (IJRISAT), 2022)
The protein content of freshwater bivalve, Corbicula striatella was studied after exposure to endosulfan. Overall depletion in proteins content in mantle, foot, gill, digestive gland and whole body was observed. The study was carried for median lethal (0.314) and sublethal (0.068).ISO 14001 standards of EMS.